2010
DOI: 10.1136/vr.b4800
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, management and health of donkeys in the UK

Abstract: In this paper, the management and health problems of donkeys on loan to independent carers from The Donkey Sanctuary are characterised, and the demographics of the UK's donkey population are described using data from a variety of sources. All carers that fostered a donkey from The Donkey Sanctuary between September 2004 and August 2005 (1432 donkeys) were surveyed using a postal questionnaire requesting information about the donkey, its premises, daily care, health and preventive medicine. The response rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
3
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 24 publications
5
51
3
8
Order By: Relevance
“…Foot disorders and arthritis are common in aged donkeys in the UK (Cox et al 2010;Morrow et al 2011). Therefore, unsurprisingly, lameness represented the highest proportion of veterinary surgeons' donkey caseload in the current study and a high proportion of donkey owner respondents had owned a donkey with foot and limb problems.…”
Section: Discussionmentioning
confidence: 72%
“…Foot disorders and arthritis are common in aged donkeys in the UK (Cox et al 2010;Morrow et al 2011). Therefore, unsurprisingly, lameness represented the highest proportion of veterinary surgeons' donkey caseload in the current study and a high proportion of donkey owner respondents had owned a donkey with foot and limb problems.…”
Section: Discussionmentioning
confidence: 72%
“…It is estimated that there are currently about 8900 donkeys ( Equus asinus ) 1, an unknown number of mules ( E . asinus × caballus ) and just under 1 million horses ( Equus caballus ) 2 in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…The major problems facing donkeys in the UK are obesity (Cox and others 2010) and the health conditions associated with it, including laminitis (Morrow and others 2011), equine metabolic syndrome (Du Toit and Trawford 2010) and a predisposition to hyper­lipaemia (Burden and others 2011). Appropriate nutrition is the key to weight control, and recent research has shown that the donkey requires significantly less energy per day for maintenance than a pony of the same size.…”
Section: Nutritional Requirementsmentioning
confidence: 99%